A New Isoflavone from Lomariopsis guineensis (Underw.) Alston - Al-Tannak, Naser F.; Al Ali, Abdullah; Santali, Eman; C. J. Clements; A. I. Gray; J. O. Igoli (Emirates Journal of Food and Agriculture, 2023)
Aim/background: Lomariopsis guineensis (Underw.) Alston is an epiphytic climbing fern. It is widely distributed in Africa where it is also used in traditional medicine and as food. There are no previous reports of any constituents of the plant, hence this study to isolate any phytoconstituents. Method: The ethyl acetate extract of the leaves was subjected to column chromatography and isolated constituents were characterized using nuclear magnetic resonance and mass spectrometry. Results: Three compounds were isolated and identified as cycloartenol, pheophytin A and a new isoflavone (5, 7-dihydroxy-4′ methoxy-6,8-dimethylisoflavone). Conclusion: Three phytochemicals including a new isoflavone are reported from the plant for the first time. Keywords: Isoflavone; Lomariopsis guineensis; pheophytin A; cycloartenol; antitrypanosomal assay